"Longitudinal Oral Health‐Related Quality of Life in maxillary mini dental implant overdentures after 3 years in function". Issue 1 (31st October 2020) - Van Doorne, Luc; Fonteyne, Ester; Matthys, Carine; Bronkhorst, Ewald; Meijer, Gert; De Bruyn, Hugo
Abstract: Objectives: Longitudinal evaluation of Oral Health‐Related Quality of Life (OHRQoL) during treatment of flaplessly placed, one‐piece mini‐dental‐implants (MDIs) for maxillary overdentures is rarely investigated, nor is the impact of MDI failures. Material and methods: This multicenter prospective cohort study evaluated the 3‐year outcome of 5–6 MDIs in the edentulous maxilla in patients above 50 years with dentate mandible. Provisional dentures were provided before final prosthetic connection was established at 6 months. Postoperative discomfort was assessed using a visual analogue score (VAS). OHRQoL was investigated using the Oral Health Impact Profile (OHIP)‐14 at baseline (preoperatively), postoperatively, post‐prosthetic connection and after 3 years in function. Results: 164 (78.4%) of the 204 placed MDIs were still in situ after 3 years, in 29/31 patients. Two patients lost 5/6 MDIs resulting in two prosthetic failures (6.45%). With regard to pain, a score of 4.1/10 ( SD 2.8) was recorded on day 1, and 1.1/10 ( SD 1.7) on day 7. A decrease in total OHIP‐14 scores was observed postoperatively (15.6; SD 12.8) as compared to baseline (21.3; SD 13.1), with improvement of OHRQoL. Furthermore, this was statistically significant at connection of the final prosthesis (7.3; SD 6.7) ( p  = .006). The OHIP‐14 improved less ( p  = .011) when experiencing one or more implant losses (9.5; SD : 9.85), in comparison with no implant loss (20.7; SD : 13.97). A failure of one MDI did not affect OHIP‐14 score ( p  = .658); however, multiple failures did ( p  = .007). Conclusion: Maxillary MDI overdenture treatment yields significant OHRQoL improvement when at least 5 MDIs survive, preserving functional comfort.